Maraviroc versus Efavirenz, Both in Combination with Zidovudine-Lamivudine, for the Treatment of Antiretroviral-Naive Subjects with CCR5-tropic HIV-1 Infection - Cooper, David A.; Heera, Jayvant; Heera, Jayvant; Goodrich, James; Tawadrous, Margaret; Saag, Michael; DeJesus, Edwin; Clumeck, Nathan; Walmsley, Sharon; Ting, Naitee; Coakley, Eoin; Reeves, Jacqueline D.; et al. (The Journal of infectious diseases, 2010)
Background. The MERIT (Maraviroc versus Efavirenz in Treatment-Naive Patients) study compared maraviroc and efavirenz, both with zidovudine-lamivudine, in antiretroviral-naive patients with R5 human immunodeficiency virus type 1 (HIV-1) infection. Methods. Patients screened for R5 HIV-1 were randomized to receive efavirenz (600 mg once daily) or maraviroc (300 mg once or twice daily) with zidovudine-lamivudine. Coprimary end points were proportions of patients with a viral load <400 and <50 copies/mL at week 48; the noninferiority of maraviroc was assessed. Results. The once-daily maraviroc arm was discontinued for not meeting prespecified noninferiority criteria. In the primary 48-week analysis (n=721), maraviroc was noninferior for <400 copies/mL (70.6% for maraviroc vs 73.1% for efavirenz) but not for <50 copies/mL (65.3% vs 69.3%) at a threshold of −10%. More maraviroc patients discontinued for lack of efficacy (11.9% vs 4.2%), but fewer discontinued for adverse events (4.2% vs 13.6%). In a post hoc reanalysis excluding 107 patients (15%) with non-R5 screening virus by the current, more sensitive tropism assay, the lower bound of the 1-sided 97.5% confidence interval for the difference between treatment groups was above −10% for each end point. Conclusions. Twice-daily maraviroc was not noninferior to efavirenz at <50 copies/mL in the primary analysis. However, 15% of patients would have been ineligible for inclusion by a more sensitive screening assay. Their retrospective exclusion resulted in similar response rates in both arms Trial registration. ClinicalTrials.gov identifier: (NCT00098293).